Editorial Volume 6, Issue 1 - Martie Gillen (Journal of Financial Therapy, 2015)
The editorial introduces Dr. Martie Gillen as the associate editor of book reviews and professional profiles for the Journal of Financial Therapy. The editorial overviews the empirical research and theoretical oriented manuscripts along with the professional profiles and book reviews featured in volume 6, issue 1 of the Journal of Financial Therapy.
Keywords: financial therapy; solution focused financial therapy; solution focused; theory of planned behavior; earned income tax credit